Adult Learners Meaning Making of an Adult Education Master’s Degree Program - Royce Ann Collins; Susan Yelich Biniecki; Constance Carpenter; Keondria McClish (Adult Education Research Conference, 2018)
This paper discusses the results of a qualitative research study, which explored how adult learners make meaning of their lived experiences in an adult education master’s degree program. Eportfolio data and reflection requirements grounded within concepts of megacognition informed the assessment
Keywords: reflection; eportfolio; metacognition; assessment